Temettüat Defterleri’ ne göre Erzurum şehri ( 1260/ 1844 ) - Çoruh, Haydar (My University, 1997)
unknown
Keywords: Doğu ve Güneydoğu Anadolu bölgesi; Erzurum; Tarih; Tarih_Osmanlı İmparatorluğu; Türkiye